Type II collagen is a target antigen of clonally expanded T cells in the synovium of patients with rheumatoid arthritis. Issue 7 (1st July 1999) - Sekine, Taichi; Kato, Tomohiro; Masuko-Hongo, Kayo; Nakamura, Hiroshi; Yoshino, Shin-ichi; Nishioka, Kusuki; Yamamoto, Kazuhiko
Abstract : OBJECTIVE: To investigate whether type II collagen (CII) is recognised by oligoclonally expanded synovial T cells of patients with rheumatoid arthritis (RA). METHODS: Peripheral blood mononuclear cells (PBMC) from 15 RA patients were stimulated with CII in vitro. T cell clones expanded by such stimulation were compared with the clonally expanded synovial T cells by using T cell receptor (TCR) B chain gene specific reverse transcription-polymerase chain reaction and subsequent single strand conformation polymorphism analyses. RESULTS: Stimulation of the heterogeneous peripheral T cells with CII induced clonal expansion of T cells. In three of 15 patients, a proportion of these clones (approximately 17% to 25%) was found to be identical to expanded T cell clones in the synovium in vivo. CONCLUSION: T cell clones that had TCR CDR3 sequences identical to those induced by purified CII were found in a proportion of RA patients. This finding suggests that CII is recognised by T cells that accumulate clonally in RA joints. Oligoclonal T cell expansion in RA joints is probably driven, at least in part, by intra-articular components such as CII.